Experimental investigation of forced convective heat transfer in nanofluids - Tan, Kah Kee. (2011)
Nanofluids are suspensions of nanoparticles (1 to 100 nm) in traditional base fluids and are seen as potential candidates to enhance heat transfer in various engineering applications.